Magnetic nanoparticles in regenerative medicine: what of their fate and impact in stem cells?. (August 2020) - Van de Walle, A.; Perez, J.E.; Abou-Hassan, A.; Hémadi, M.; Luciani, N.; Wilhelm, C.
Abstract: With advancing developments over the use of magnetic nanoparticles in biomedical engineering, and more specifically cell-based therapies, the question of their fate and impact once internalized within cells remains crucial. After highlighting the regenerative medicine applications based on magnetic nanoparticles, this review documents their potential cytotoxicity and, more importantly, underscores their valuable features for stem cell differentiation. It then focuses on the transformations magnetic nanoparticles might experience in cells, mainly consisting in their progressive degradation, and assesses the practical pitfalls related to this degradation. First, it may result in a loss of long-term theranostic potential, and second, it drives an adaptation of the cell metabolism to the released iron. Overall, this review demonstrates that magnetic nanoparticles present undeniable interest for stem cell-based biomedical applications; however, each nanoparticle/cell system must be carefully considered for a safe medical use. It also clearly demonstrates that the biodegradation of the nanoparticles and the cell response to the released iron must be systematically assessed. Graphical abstract: Image 1 Highlights: The potential benefits of magnetic nanoparticles for regenerative medicine applications are undeniable. Is there a direct toxicity upon internalization in cells? In particular regarding stem cells differentiation? Stem cells can assimilate the nanoparticles, store the iron released from their degradation in endogenous ferritin and adapt their iron metabolism accordingly. Overall, balancing the long-term cellular risks and theranostic benefits across the use of magnetic nanoparticles within stem cells for regenerative medicine must be carefully faced.